Mobility as capability : women in the Indian informal economy - Menon, Nikhila (New Delhi Cambridge University Press, 2020)
This book highlights accounts of women workers to capture the domains of gendered mobility, which challenges the exalted status conferred on women in the Kerala model of development. It contests and deconstructs the development discourse which considers women's work mobility as an indicator of autonomy and agency using Capability Approach. The concept of 'transformational mobility' and its measurement introduced in the book advances the understanding of mobility, autonomy and agency and the intersectionality in the context of gender and work. Through an in-depth exploration of lived experiences of informal women workers the author illustrates how patriarchal structures are shaped and reinforced by work places, markets and the state. The central question is - can we steer development policies to facilitate collective capabilities for women where informal work arrangements are becoming the norm?
Keywords: Women - Employment - India; Economic development